Authority of the United Nations to 'intervene' within the meaning of Article 2(7) of the Charter - Gilmour, David R. (The University of Edinburgh, 1965)
No subject within the discipline of Public International Law is more topical at the present time than that of intervention. The war in Viet-Nam and the American action in the Dominican Republic have, once again, brought this most controversial subject to the fore. These are, however, examples of unilateral intervention and it is not the purpose of this study to elaborate the principles of law, if any, which apply to them. The present purpose is to study certain aspects of the law of intervention under the Charter of the United Nations, itself a topic which engenders a lot of feeling and which has been the subject of controversy ever since the inception of the Organization. The present study is timely, the United Nations itself at last having turned its thoughts to the study of this question. It is hoped that the following study may shed some light on the practice which has ensued in the organs of the United Nations and the trends which have developed therein in this regard.
The authority of the United Nations to 'intervene' within the meaning of Article 2(7) of the Charter